How does protectionism impact multinational firm reshoring? Evidence from the UK - Temouri, Yama; Pereira, Vijay; Delis, Agelos; Wood, Geoffrey (Springer, 2023)
There is growing interest in the nature and possible extent of de-globalization. This paper explores the impact that protectionist measures have on multinational enterprise (MNE) reshoring back to the UK. Besides taking into account the global trends indicating a return to protectionism, the existing literature highlights various firm-level and structural country-level determinants of reshoring decisions. We test a conceptual model with parent-subsidiary firm-level data for the period 2009 to 2017. We conclude that firms that are more sensitive to wage costs in their overseas subsidiaries were more likely to reshore. We did not find that more capital-intensive firms had a higher propensity to reshore. We find that our results are mostly driven from UK MNEs with subsidiaries in EU. This result has clear implications for a potential Brexit effect. Theoretically, we base our findings in transactional cost economics to help explain why different types of firms behave in the way they do, and why different types of firms may respond in quite different ways to the same mix of institutions.
Keywords: Multinational Enterprises; Reshoring; Protectionism; UK